STRENGTHENING SCHOOL MANAGEMENT THROUGH THE PRINCIPLES OF GOOD GOVERNANCE IN PUBLIC ADMINISTRATION - Aurelia, Azahra Clarista; Ningrum, Sekar Cahya; Hanim, Auliana Fathiya; Hakiki, Fifi Auliya; Sa’dun, Muhammad; Sulistyo, Sabrina Aufara (Jurnal Penelitian Pendidikan Indonesia, 2025)
This study aims to analyze the strengthening of school management through the application of good governance principles in the context of public administration. School-Based Management (SBM) as an educational decentralization approach requires strengthening good governance to achieve optimal effectiveness. Through literature review, this research examines the implementation of good governance principles, namely accountability, transparency, participation, and performance-based evaluation in school management. The analysis results show that the implementation of accountability principles in BOS fund management still faces challenges in the form of minimal reporting transparency and lack of public oversight. Stakeholder participation in school decision-making is not optimal due to limited understanding of school committee roles and low community policy literacy. Performance-based evaluation systems in schools have not been implemented systematically and comprehensively. The integration of good governance principles in SBM has great potential to improve school management quality, but requires strengthening the capacity of principals as public managers, increasing transparency through digitalization of reporting, and empowering community participation. This study recommends the need for good governance-based management training for principals, development of transparent online reporting systems, and strengthening the role of school committees as a form of social control.